Evaluation of macro nutrient, fatty acid and microbiology aspect of mackerel tuna crackers - Sukma Elida; Hardinsyah Hardinsyah; Eny Palupi; Ahmad Sulaeman (AcTion: Aceh Nutrition Journal, 2025)
Stunting is a health issue related to chronic malnutrition over 1000 days of life.  Fulfilling the nutritional needs of pregnant women through fish consumption has been recommended in several studies. In Indonesia, mackerel tuna is a popular fish type at affordable prices. We developed mackerel tuna crackers as a nutritional product innovation for pregnant women made from mackerel tuna meat, eggs, and various spices. This product was developed as a food supplement for pregnant women. This study aimed to evaluate the macronutrients, fatty acids, and microbiological aspects of the product. Laboratory analyses were performed at the Integrated Laboratory of the IPB University. The results showed that the protein content of the product was highest in formula 1 (39,71%), meeting 54% of the protein requirement of pregnant women according to the IOM 2005 recommendation and 44,12% protein requirement of pregnant women according to AKG 2019. The total omega-3 content was highest in formula 2 (1,18%), and the total omega-6 content was highest in formula 3 (10,78%). The results of the microbiological test showed that all product samples were safe according to SNI 7988:2009. Further studies on the efficacy of mackerel tuna crackers as a nutritional intervention in pregnant women are urgently required.